(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This thesis highlights the importance of implementing modern management technologies in enterprises and their impact on efficiency. It also analyzes the issues of effective use of resources, optimization of production processes, and increasing competitiveness through improving the management system.